Deadlock or Transformational Change? Exploring Public Discourse on REDD+ across Seven Countries - Gregorio, M. di; Brockhaus, Maria; Cronin, T.; Muharrom, E.; Mardiah, S.; Santoso, L. (MIT Press, 2015)
This article investigates the public discourses on reducing emissions from deforestation and forest degradation (REDD+) across seven countries, to assess whether they support policy reforms. We argue that transformational discourses have at least one of these characteristics: they advocate specific policy reforms that address the drivers of deforestation and forest degradation; take into account the potential risks of a REDD+ mechanism; go beyond technocratic solutions to reduce emissions; and explicitly challenge existing power relations that support drivers of deforestation. The evidence indicates the predominance of win-win storylines, a lack of engagement by state actors with debates on the potential negative socioeconomic outcomes of REDD+, and little attention to the drivers of deforestation. The article concludes that to achieve a shift toward transformational public discourse, reformist policy actors and the media need to engage dominant policy actors in debates about how to reduce pressure on the forest.